Personality and Ethics on Online Labor Markets: How mood influences ethical perceptions - Evangelos Mourelatos (ZBW - Leibniz Information Centre for Economics, 2021)
This research explores whether there is a link between mood and ethical perceptions in online labor markets. The experimental design allows to track the determinants of the underlying mechanism of individuals' behavior within and without the treatment context. By using OLS estimation methods the paper also provides empirical evidence for several statistically significant effects of personality traits on ethical perceptions, value co-creation and relationship quality. In general, the positive mood manipulation lead to an increase of individuals' ethical perceptions, value co-creation and relationship quality. These findings suggest that mainly the effect of positive mood on the outcomes operates through the trait of agreeableness. Contributions to the ethical perception, mood research and online-economy literature are discussed
Keywords: D91; D87; D53; D23; D01; 330; ethical perception; value co-creation; mood; personality; online labor markets